Validity of ultrasonograph muscle thickness measurements for estimating muscle volume of knee extensors in humans - Miyatani, Masae; Kanehisa, Hiroaki; Kuno, Shinya; Nishijima, Takahiko; Fukunaga, Tetsuo (European journal of applied physiology, 2002)
This study aimed to investigate the suitability of using ultrasonograph muscle thickness (MT) measurements to estimate the muscle volume (MV) of the quadriceps femoris as an alternative approach to magnetic resonance imaging (MRI). The subjects were 46 men aged from 20 to 70 years who were randomly allocated to either a validation or a cross-validation group. In the validation group, multiple and simple regression equations, which used a set of MT values determined at mid-thigh and thigh length (1) and the product of pi, (MT/2)2, and l [pi x (MT/2)2 x l], respectively, as independent variables, were derived to estimate the MV measured by MRI. Because the two equations were cross-validated, the data from the two groups were pooled to generate the final prediction equations: MV (cm3)=(MT x 311.732)+(l x 53.346) -2058.529 as the multiple regression equation and MV (cm3) = [pi x (MT/ 2)2 x l] x 1.1176+663.040 as the simple regression equation. In the multiple regression equation, MT explained 75% of the variation in the MV measured by MRI. The r2 and the standard error of the estimate (SEE) of the equations were 0.824 and 175.6 cm3 (10.6%), respectively, for the multiple regression equation and 0.829 and 173.7 cm3 (10.5%), respectively, for the simple regression equation. Thus, the present results indicate that ultrasonograph MT measurements at mid-thigh are useful for estimating the MV of knee extensors. However, the observed SEE values suggest that the prediction equation obtained in this study may be limited to population studies rather than individual assessments in longitudinal studies.